ChemInform Abstract: Amidation of Esters with Amino Alcohols Using Organobase Catalysis. Issue 12 (March 2015) - Caldwell, Nicola; Campbell, Peter S.; Jamieson, Craig; Potjewyd, Frances; Simpson, Iain; Watson, Allan J. B.
Abstract BEMP is an efficient catalyst for reactions of amino alcohols with dimethyl carbonate and a variety of methyl esters.